Facile synthesis of indolizino[3, 4, 5-ab]isoindoles by an acid-induced cyclization of 1, 2-di(1H-pyrrol-2-yl)benzenes. Issue 41 (7th October 2015) - Kuzuhara, Daiki; Miyake, Satoshi; Moriyama, Hirotake; Tamura, Yuto; Aratani, Naoki; Yamada, Hiroko
Graphical abstract: Abstract: The new synthetic method of indolizino[3, 4, 5- ab ]isoindoles (INIs) by an acid-induced intramolecular cyclization of 1, 2-di(1 H -pyrrol-2-yl)benzenes has been developed. This protocol can be applied to the preparation of INI derivatives with electron-donating and -withdrawing groups as well as azaINIs.